The Effects of Perceived Service Quality and Satisfaction on Brand Loyalty: The Mediating Role of Coffee Shop Customer Trust in Bali - Wahyuni, Ni Made; Indiani, Ni Luh Putu (Universitas Mercu Buana, 2025)
Objectives: Competition, turbulence, changes in customer preferences have an effect on customer loyalty. Although the topic of the relationship between service quality and customer satisfaction on customer loyalty has been widely researched, there are still factors that are important to consider in the mechanism of the relationship.Methodology: The main objective of this study is to provide a reliable framework for coffee shop businesses. Using a sample of 145 coffee shop visitors, a model was developed and then tested with Partial Least Square (PLS) to examine the interaction of multiple variables and mediation effects.Finding: The empirical results are considered satisfactory as they offer knowledge insights into how to maximize service quality and customer satisfaction on customer loyalty. In particular, trust is an important mediator of the relationship of service quality and customer satisfaction on brand loyalty. This study proves that quality service and the importance of customer satisfaction significantly positively affect the level of trust and customer loyalty. The practical implication is that the mediating variable in this study is a variable that coffee shop context managers can manage.Conclusion: The results of this study indicate that the higher the service quality and customer satisfaction, the higher the consumer trust in the company. This shows that service quality and customer satisfaction are able to predict trust.